Effects of fully-established Sure Start Local Programmes on 3-year-old children and their families living in England: a quasi-experimental observational study. - Melhuish, E; Belsky, J; Leyland, A; Barnes, J (2008)
BACKGROUND: Sure Start Local Programmes (SSLPs) are area-based interventions to improve services for young children and their families in deprived communities, promote health and development, and reduce inequalities. We therefore investigated whether SSLPs affect the wellbeing of 3-year-old children and their families. METHODS: In a quasi-experimental observational study, we compared 5883 3-year-old children and their families from 93 disadvantaged SSLP areas with 1879 3-year-old children and their families from 72 similarly deprived areas in England who took part in the Millennium Cohort Study. We studied 14 outcomes-children's immunisations, accidents, language development, positive and negative social behaviours, and independence; parenting risk; home-learning environment; father's involvement; maternal smoking, body-mass index, and life satisfaction; family's service use; and mother's rating of area. FINDINGS: After we controlled for background factors, we noted beneficial effects associated with the programmes for five of 14 outcomes. Children in the SSLP areas showed better social development than those in the non-SSLP areas, with more positive social behaviour (mean difference 0.45, 95% CI 0.09 to 0.80, p=0.01) and greater independence (0.32, 0.18 to 0.47, p<0.0001). Families in SSLP areas showed less negative parenting (-0.90, -1.11 to -0.69, p<0.0001) and provided a better home-learning environment (1.30, 0.75 to 1.86, p<0.0001). These families used more services for supporting child and family development than those not living in SSLP areas (0.98, 0.86 to 1.09, p<0.0001). Effects of SSLPs seemed to apply to all subpopulations and SSLP areas. INTERPRETATION: Children and their families benefited from living in SSLP areas. The contrast between these and previous findings on the effect of SSLPs might indicate increased exposure to programmes that have become more effective. Early interventions can improve the life chances of young children living in deprived areas.